2016
DOI: 10.1186/s13568-016-0269-x
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive genomic and phenotypic metal resistance profile of Pseudomonas putida strain S13.1.2 isolated from a vineyard soil

Abstract: Trace metals are required in many cellular processes in bacteria but also induce toxic effects to cells when present in excess. As such, various forms of adaptive responses towards extracellular trace metal ions are essential for the survival and fitness of bacteria in their environment. A soil Pseudomonas putida, strain S13.1.2 has been isolated from French vineyard soil samples, and shown to confer resistance to copper ions. Further investigation revealed a high capacity to tolerate elevated concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…The higher abundance of iron complex outer membrane receptor protein in the rhizosphere indicates the enrichment of Gram-negative bacteria, which outer membrane receptor system for siderophore-mediated Fe transportation (Ahmed and Holmström, 2014). The CzcA protein has been reported to be involved in the efflux of heavy metals ions (Nies, 2000) and was also present in metal resistance Pseudomonas putida S13.1.2 isolated from a vineyard soil (Chong et al, 2016). Rhizosphere offers a variety of abiotic stress, including temperature fluctuations, salinity, osmolarity, oxygen concentration, and nutrient concentration, to the bacteria; RNA polymerase sigma-70 factors play relevant roles in adapting to different kinds of stresses (Martínez-Salazar et al, 2009;Mishra et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The higher abundance of iron complex outer membrane receptor protein in the rhizosphere indicates the enrichment of Gram-negative bacteria, which outer membrane receptor system for siderophore-mediated Fe transportation (Ahmed and Holmström, 2014). The CzcA protein has been reported to be involved in the efflux of heavy metals ions (Nies, 2000) and was also present in metal resistance Pseudomonas putida S13.1.2 isolated from a vineyard soil (Chong et al, 2016). Rhizosphere offers a variety of abiotic stress, including temperature fluctuations, salinity, osmolarity, oxygen concentration, and nutrient concentration, to the bacteria; RNA polymerase sigma-70 factors play relevant roles in adapting to different kinds of stresses (Martínez-Salazar et al, 2009;Mishra et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of Methylobacterium has been recently reported by Portillo et al (2016) in the grape surface of different varieties; and Ps. putida , present in grapevine soil, is very important because its capacity of resisting different metal contamination ( Chong et al, 2016 ). Furthermore, the identification of Bacillus subtilis applied from grapevine until the AF depletion should be taken into consideration in future works.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that long-term association with metal-hyperaccumulator plant leads to local adaptation by Pseudomonas endophytes 50 . Copper and arsenic resistant Pseudomonas strains have been frequently isolated from the vineyard environment 51 , 52 . Indeed, vineyards have been treated with copper-containing pesticides to control plant pathogens 53 as well as with sodium arsenate till the end of the last century, which may still be present in vineyard soils 54 .…”
Section: Resultsmentioning
confidence: 99%